Accurate track control of unmanned underwater vehicle under complex disturbances - Haohua CHEN; Hong ZHAO; Ning WANG; Chen GUO; Ting LU; Ning WANG (Zhongguo Jianchuan Yanjiu, 2022)
ObjectivesThis paper presents a non-singular terminal sliding mode track control method based on a finite-time disturbance observer to solve the problem of accurately tracking and controlling an the 3D trajectory of an unmanned underwater vehicle under complex external disturbances.MethodsA non-singular terminal sliding mode track controller is designed to ensure that the tracking error converges to zero accurately within a limited time. A finite-time disturbance observer is designed to improve the anti-jamming ability of the system under external multidimensional time-varying disturbances.ResultsThe Lyapunov function is used to prove that the designed control strategy can remain stable for a limited time. MATLAB is used for the simulation experiment, and a comparison with the backstepping sliding mode control method under step disturbance shows that the method presented in this paper achieves accurate trajectory tracking.ConclusionsThe results of this paper can provide a solution for accurately tracking the 3D trajectories of unmanned underwater vehicles.